Manufacturing of graded titanium scaffolds using a novel space holder technique - Yunhui Chen (Bioactive Materials, 2017)
To optimize both the mechanical and biological properties of titanium for biomedical implants, a highly flexible powder metallurgy approach is proposed to generate porous scaffolds with graded porosities and pore sizes. Sugar pellets acting as space holders were compacted with titanium powder and then removed by dissolution in water before sintering. The morphology, pore structure, porosity and pore interconnectivity were observed by optical microscopy and SEM. The results show that the porous titanium has porosity levels and pore size gradients consistent with their design with gradual and smooth transitions at the interfaces between regions of differing porosities and/or pore sizes. Meanwhile, the porous titanium has high interconnectivity between pores and highly spherical pore shapes. In this article we show that this powder metallurgy processing technique, employing the novel sugar pellets as space-holders, can generate porous titanium foams with well-controlled graded porosities and pore sizes. This method has excellent potential for producing porous titanium structures for hard tissue engineering applications.